INDEPENDENCE AND PERFORMANCE OF THE DEGREE PRIMARY SCHOOL TEACHER (Study of Social Reality Independence and Teacher Performance Open University Graduates in Bojonegoro Region) - *, Mujadi (IJRDO- Journal of Educational Research, 2017)
Whether or not the quality of education is very dependent on who is running the education itself. The level of student achievement is also highly dependent on the quality of the teachers who carry out the learning to the learners. Education in Indonesia has made a new paradigm in addressing the low quality of education and achievements of learners through increasing academic qualifications for teachers who teach in primary school to high-school level. Improvement of qualification of teachers specifically focused on the most elementary school teachers from the School of Teacher Education qualification (SPG) and the Diploma -2 -1 to Strata education elementary school teacher (PGSD). To expedite the qualification of primary school teachers in Indonesia is required college organizes undergraduate program (S-1) PGSD with considerable capacity. To realize this the only alternative is the Open University as an institution of higher education distance that can accommodate a large number of students without being limited by space and time. This is because the Open University uses distance learning system with the concept of self-learning, so teachers who studied at the Open University does not have to leave his job as a teacher in the learning process. With the concept of self-owned learning expected of teachers graduated from S-1 PGSD Open University is able to carry out his work in the learning process in school full independence in the face of all obstacles in school and in the community. The extent to which the independence of teachers is implemented in the learning process? And how the performance of primary school teachers graduated from the Open University in the school ?. Researchers are trying to find out "Independence and Elementary School Teacher Performance Tier One", Review of Social Reality Independence and Teacher Performance Open University Graduates in Bojonegoro Region. The respondents of teachers drawn from schools in urban areas to the suburbs in accordance with the criteria and character study. Independence (autonomy) and teacher performance is the focus of research. This research is using qualitative method in the analysis of the data and produced a substantive theory development. Data taken by observation, monitoring, and interviews in accordance with the method of qualitative research, the data on the independence of appropriate teacher competency responsibility, initiative, ability, satisfaction, and planning with indicators exist, and performance data of teachers regarding pedagogic , personality, social, and professional with accompanying indicators. The role of informants consisting of Bojonegoro district education offices, school principals, peers, school committees, and learners are very significant in providing data completeness and refinement of research results. While the implications for existing theories is to provide a basic understanding of independence, according to some experts and based on existing research results, that independence is "independence means the state or the manner